Pharmacological basis for the folkloric uses of Buxus wallichiana in gastrointestinal, respiratory and vascular disorders - Hussain, Musaddique; Raza, Shahid Masood; Janbaz, Khalid Hussain (Bangladesh Journal of Pharmacology, 2015)
In vitro study was carried out to explore the pharmacological basis of crude extract of Buxus wallichiana for its folkloric uses in gastrointestinal, respiratory and vascular disorders. In jejunum preparations, crude extract (0.03 ± 1.0 mg/mL) caused a transient spasmogenic effect followed by the spasmolytic effect at higher doses (3.010 mg/mL). In atropinized jejunum preparation, crude extract inhibited the spontaneous and K+ (80 mM)-induced contraction, suggesting that spasmolytic effect is mediated through the Ca+2-channel blockade. The Ca+2-channel blockade effect was confirmed when pretreatment of tissue with extract produced a dose-dependent shift in Ca+2 concentration-response curves to the right, similarly as verapamil. Furthermore, crude extract exhibited non-specific relaxant effect on carbachol- (1 µM) and K+ (80 mM)-induced tracheal contractions, suggesting the coexistence of anticholinergic and Ca+2-antagonistic properties. Moreover, it relaxed the K+ (80 mM)- and phenylephrine (1 µM)-induced contraction in rabbit aorta, suggesting the Ca+2-channel blockade. These findings may validate the folkloric uses of B. wallichiana in constipation, bronchitis, asthma and hypertension.